In Vitro Inhibitory Effect Of Fungicides And Boiagents On Mycelial Growth Of Fungi Associated With Chilli Seeds (Journal of Plant Disease Sciences, 2022)
Chilli (Capsicum annuum L.) is the important commercial vegetable crop of India belongs to solanceae family.Chilli seeds harbours many fungal pathogens which are seed transmitted often reduce the germination ability and substantially reduce the productive capacity. Hence assessment and management of seed borne fungi of chilli is important. Fungicides were tested against seed born fungi of chilli in vitro by employing poisoned food technique. Thiram (0.3%) and Carboxin + Thiram (0.3%) were found most effective fungicides recorded 100 % mycelial growth inhibition of all associated seed borne fungi followed by Thiram + Carbendazim (0.3%) and Thiram + Captan (0.3%). Bio agents were also tested against seed borne fungi of chilli employing dual culture technique. The fungal bioagent Trichoderma harzianum was found most effective against seed borne fungi tested followed by Trichoderma asperellum.In respect of bacterial bio agents Pseudomonas fluorescence was found most effective followed by Bacillus subtilis.
Keywords: Bioagents; Chilli; Efficacy; Fungicides